Ask a neurologist: What primary care providers ask, and reducing referrals through eConsults. Issue 3 (June 2018) - Bradi, Ana C.; Sitwell, Lucian; Liddy, Clare; Afkham, Amir; Keely, Erin
Abstract : Background: Access to neurology consultation is limited by high demand and urgency of the presentation. Champlain BASE TM (Building Access to Specialists through eConsultation) (eConsult service) aims to increase access through direct communication between primary care providers (PCPs) and specialists. Rapid responses to PCP questions can guide management and sometimes relieve the need for a formal consultation. We reviewed which topics were frequently addressed, the types of questions asked, and the effect on primary care for the patient. Methods: This is a retrospective review of 387 consecutive questions submitted to the Champlain BASE TM service between May 2011 and January 2015 and the data generated from routine use and PCP exit surveys. Questions were categorized by topic and type and analyzed quantitatively. This included time required to answer each question and effect on plans for traditional referral and clinical course of action. Results: The top 5 topics were headache (17%), incidental imaging findings (11%), numbness/tingling (11%), seizure (9%), and cerebrovascular disease (CVD) (9%). Fifty-one percent were related to diagnosis (choice of test, imaging interpretation, symptom interpretation), 23% to drug treatment (choice, adverse effects, prescribing instructions), and 17% to management (general, need for referral). Eighty-eight percent of questions took less than 10 minutes of specialist time to answer, and 80% were answered within 1 day. eConsults decreased face-to-face referrals by 50%. In 54% of cases, the PCP received information for a new course of action. Conclusions: We found that an eConsult service provides timely access to neurologists and can divert half of intended face-to-face consultations. The most common questions posed by PCPs regarded diagnosis and drug therapy for headaches, seizures, altered sensation, and CVD. eConsult services could provide guidance for continuing medical education planning in neurology.